PENGARUH KOMPETENSI, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. ZULU ALPHA PAPA DI KOTA MAKASSAR - Rahmadianti, Rahmadianti; Jusriadi, Edi (COMPETITIVENESS, 2018)
The purpose of this research is (1) To analyze and prove the influence of competence on the performance of PT employees. Zulu Alpha Papa in Macau City. (2) To analyze and prove the influence of work discipline on the performance of PT employees. Zulu Alpha Papa in Makassar City. (3) To analyze and prove the effect of job satisfaction on the performance of PT employees. Zulu Alpha Papa in Makassar City. (4) To analyze and know the variables that predominantly affect the performance of PT employees. Zulu Alpha Papa in Makassar City.This type of research is quantitative research with an exoplanet approach. The data sources in this study are all employees of PT. Zulu Alpha Papa in Makassar City. The data was obtained through questionnaires, interviews and observations, which were obtained directly from respondents on a likert (ordinal) scale with the summed rating method. The analysis method used in this research is quantitative descriptive method, through regression testing by conducting validity and reliability test of question items of each variable as well as assumption test.The results showed that (1) competency has a significant positive influence on employee performance with P = 0.039< 0.05 with a coefficient value of 0.228, this coefficient shows that the better the competency of employees, the performance of PT employees. Zulu Alpha Papa Makassar will increase. (2) Work discipline has a significant positive influence on employee performance with P = 0.002<0.05 with a coefficient of 0.554, This coefficient shows that the higher the employee's work discipline, the employee performance of PT. Zulu Alpha Papa Makassar will also increase. (3) Job satisfaction has no significant effect on employee performance with P = 0.195> 0.05 with a coefficient value of 0.146, this coefficient indicates that employee job satisfaction does not affect employee performance at PT. Zulu Alpha Papa Makassar. (4) and the variable that has the dominant effect on employee performance is the discipline of work, this can be seen from the beta value of 0.618 greater than other variables. Keywords: Competence, Discipline, Job Satisfaction, and Performance.